THE ERROR ANALYSIS OF PRONUNCIATION OF NOUN AND VERB IN READING ALOUD AT THE SECOND SEMESTER OF STIA BALA PUTRA DEWA PALEMBANG YEAR 2021 /2022 - Fatiha, Emilda Sinar (Esteem Journal of English Education Study Programme, 2022)
This study aimed to identify students’ pronunciation errors in reading aloud by finding out how far the students’ pronunciation errors in reading aloud in plural nouns, singular verb, and the three sounds of -ed form by the students through reading aloud second level learners in the administration class of STIA Bala Putra Dewa Palembang, in the academic year 2021-2022 and also to find out the reasons of producing mispronounced in noun and verb when reading aloud. This research is descriptive qualitative. The main instrument is researcher herself. The subject of this research is the students of second-level learners of S1 Administration class. A qualitative method was used to find out the fact and the evidence of students’ pronunciation errors in reading aloud. For gathering the data, an interview and reading aloud test were conducted. This study applied descriptive analysis in analyzing the data.   Based on the findings, she found the students’ pronunciation errors occured in -ed sounds (85.21%), and present tense (70.58%). The students have difficulties in pronouncing and spelling the words with -s,-es in plural noun and singular Verb, the -ed sound in regular past tense form.  There are three reasons why the students often ignore the endings; 1).  they want to read the text quickly, so that they are assumed able reading English text, 2) the students are often forget what the teacher taught about the tenses, 3) the students’ still had interference from the mother tongue.